High dose melphalan is an adequate preparative regimen for autologous hematopoietic stem cell transplantation in relapsed/refractory lymphoma. Issue 1 (31st December 2022) - Fernández-Gutiérrez, José A.; Reyes-Cisneros, Oscar A.; Litzow, Mark R.; Bojalil-Alvarez, Lorena; Garcia-Villasenor, Elizabeth; Gómez-Gomez, Eliezer Tomas; Murrieta-Alvarez, Iván; Gomez-Almaguer, David; Gutierrez-Aguirre, Cesar H.; Karduss-Urueta, Amado J.; Ruiz-Delgado, Guillermo J.; Ruiz-Arguelles, Guillermo José
ABSTRACT: Introduction: High-dose melphalan (HD-Mel) has been successfully employed in autografting patients with multiple myeloma. An advantage of this regimen is that the total dose of Mel can be delivered in a single day, being particularly useful when non-frozen hematopoietic stem cells are employed in the autograft. Material and Methods: All consecutive patients with R/R lymphomas, both HL and NHL studied and treated at two different centers were prospectively included in a study of ASCT employing a single dose of HD-Mel (200 mg/m 2 ). A group of R/R HL or NHL autografted employing BEAM-like preparative regimens was constructed matched by diagnosis and age. The primary endpoint of the study was overall survival (OS), the secondary endpoint was event-free survival (EFS). Results: Twenty-five R/R HL/NHL patients were prospectively accrued in the study. There were 8 (32%) females, 13 (52%) patients had at least 1 adverse effect: 7 (28%) developed mucositis, 5 (20%) neutropenic fever, and 6 (24%) grade IV nausea. In the HD-Mel group, median overall survival (OS) was not achieved and OS at 36 months was 71%, the transplant-related mortality being 0%. In the control group, median OS was not achieved and the 36-month OS was 76%, results not statistically significant ( p 0.5). The EFS was also similar in both groups ( p 0.5). Conclusion: HD-Mel alone is non-inferior to a BEAM-like regimen as a preparative regimen for autografting patients with R/R HL and NHL. The regimen is adequate to graft persons with non-frozen stem cells.